Evaluation of university student's writing in the English journalism course - Yunita Susi Andriani; Hanandyo Dardjito; Silvester Goridus Sukur (Universitas Sarjanawiyata Tamansiswa, 2026)
This study aims to answer two main questions: How do the evaluation results reflect the news script writing skills of third-semester students in the Manarita STMM study program? And what aspects of writing English news scripts need to be improved by students in the Manarita program at STMM? This study applied a qualitative method, specifically a single case study design. The subjects of the study consisted of 20 students and one lecturer in charge of the English Journalism course. The results of the study showed that students still had difficulty in writing news scripts, in the straight news type. The main challenges found included difficulty in compiling news according to journalistic standards and maintaining clarity and accuracy in writing in English. The two aspects that needed the most development were the Associated Press (AP) Style and headline writing. Many students experienced obstacles in the use of grammar, punctuation, and the application of AP Style conventions, which caused inconsistencies in their news scripts. In addition, students also had difficulty in writing interesting and concise headlines so they were less able to summarize the contents of the news effectively. The results of this study emphasize the need for more in-depth training and learning related to AP Style and headline writing to improve students' news writing skills. Providing more intensive training, more specific feedback, and exposure to professional journalistic writing can help students overcome these obstacles. This study highlights the importance of strengthening English journalism learning so that students are better prepared to produce news that meets professional standards.